LncRNA and mRNA Expression Profiles in Methylprednisolone Stimulated Neural Stem Cells - Tang, Yong; Xie, Zhongyu; Ma, Mengjun; Duan, Kaidi; Li, Yuxi; Ye, Jichao (Frontiers in Neuroscience, 2021)
Spinal cord injury (SCI) is a devastating neurological disorder that affects thousands of individuals each year. Previously, our study in nonhuman primates with SCI demonstrated that methylprednisolone (MP) resulted in the dysfunction of neural stem cells (NSCs), which may help to explain the controversy roles of MP in SCI. However, the detailed mechanism is still unclear. In this manuscript, we investigated the LncRNA and mRNA expression profiles of NSCs treated with MP. A total of 63 differentially expressed LncRNA and 174 differentially expressed mRNA were identified. Gene ontology (GO) analysis showed that differentially expressed mRNA were highly associated with terms related to regulation of external stimulation, secretion and migration. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis results indicated that PI3K-Akt signaling pathway contributed to the functions of MP treated NSCs. Besides, 3899 co-expression pairs were constructed among the differentially expressed LncRNA and mRNA, among which five predicted target mRNA with the differentially expressed LncRNA were identified. These results provide greater insight into the precise mechanisms of MP mediating NSCs dysfunction in SCI.